The Use of “Organic Protein” in Feed Formulation on Intestinal and Ammonia Levels of Broiler - Sri Ratna Sari; Osfar Sjofjan (ANIMAL PRODUCTION, 2022)
The aim of this study is to determine the effect of Organic Protein as a feed ingredient on pH, viscosity and enzyme activity in the small intestine and levels of ammonia in broiler excreta. Organic Protein is a Single Cell Protein (SCP) product name from PT. Miwon Indonesia that has a protein content up to 40%. We conducted a field experiment and used DOC broilers and Organic Protein as treatment feed in a Completely Randomized Design (CRD) comprising of 5 treatments and 6 replicates, accounting for 30 experimental units. The feed treatments were basal feed T0, T1, T2, T3 and T4 added with Organic Protein 0%, 1.5%, 3%, 4.5%, and 6%, respectively. The observed variables were pH, viscosity, enzyme activity (amylase and protease) of small intestine and excreta ammonia level of broiler. The data were analyzed with ANOVA followed by Duncan’s Multiple Range Test (DMRT). The results showed the treatments have very significantly different effects (P<0.01) on the amylase and protease activities, but significantly different effects (P>0.05) on pH, viscosity of small intestine, and ammonia levels of excreta. The use of Organic Protein at a level of 4.5% gave the best results to increase enzyme activity of amylase and protease.